Pathogenic Variant in the TAF6 Gene in a Bulgarian Patient with the Ultrarare Alazami-Yuan Syndrome - Staykova, Slavyana Yaneva; Atanasoska, Maya; Gaydarova, Maria; Balabanski, Lubomir; Bradinova, Irena; Vazharova, Radoslava (Journal of Pediatric Neurology, 2023)
We present a case of a 15-year-old girl, referred for genetic analysis based on clinical evidence of intellectual disability and dysmorphic features with unknown etiology. Following genetic testing, the proband was diagnosed with Alazami-Yuan syndrome (ALYUS). ALYUS is a rare autosomal recessive disorder characterized by developmental delay, intellectual disability, poor speech, and congenital anomalies. Whole-genome sequencing and targeted analysis of 1,610 genes associated with intellectual disability and dysmorphic features were performed. One pathogenic homozygous missense variant in the TAF6 gene was identified (NM_139315.3:c.212T > C, p.Ile71Thr). The finding has been previously reported in scientific publications and detected in individuals with ALYUS. ALYUS occurs phenotypically in the presence of at least two pathogenic variants of the TAF6 gene in either homozygous or compound heterozygous state, regardless of the individual's sex. To date, seven patients from four families have been reported. To our knowledge, our proband is the first individual with ALYUS in Europe and in particular in Bulgaria. Clarification of our patient's genetic diagnosis provided precise genetic counseling for the family, allowed doctors to take appropriate measures for the proband's treatment, and gave options for disease prevention in the future offspring.
Keywords: Alazami-Yuan syndrome; TAF6 gene; intellectual disability; congenital malformations; whole-genome sequencing